Fabrication and optical properties of type‐II InP/InAs nanowire/quantum‐dot heterostructures. Issue 2 (26th November 2015) - Yan, Xin; Zhang, Xia; Li, Junshuai; Wu, Yao; Li, Bang; Ren, Xiaomin
Abstract : The growth and optical properties of InAs quantum dots on a pure zinc blende InP nanowire are investigated. The quantum dots are formed in Stranski–Krastanov mode and exhibit pure zinc blende crystal structure. A substantial blueshift of the dots peak with a cube‐root dependence on the excitation power is observed, suggesting a type‐II band alignment. The peak position of dots initially red‐shifts and then blue‐shifts with increasing temperature, which is attributed to the carrier redistribution among the quantum dots. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : Stranski–Krastanov defect‐free zinc‐blende InAs quantum dots are obtained on the side wall of ⟨110⟩ InP nanowire. A blueshift of the dot peaks with a cube‐root dependence on the excitation power is observed, suggesting a type‐II band alignment. The peak position of the dots initially red‐shifts and then blue‐shifts with increasing temperature, which is attributed to the carrier redistribution among the dots.